2009
DOI: 10.1097/jto.0b013e318194fc68
|View full text |Cite
|
Sign up to set email alerts
|

An Aortoesophageal Fistula in Patient with Lung Cancer after Chemo-Irradiation and Subsequent Esophageal Stent Implantation

Abstract: An aortoesophageal fistula (AEF) is uncommon but is frequently fatal. Most cases are attributable to a thoracic aortic aneurysm. Other common causes include malignant intrathoracic neoplasm, foreign body ingestion, endovascular stent graft repair for thoracic aortic disease, and esophageal surgery. We report a case of an AEF that developed after chemo-irradiation and subsequent esophageal stent implantation in patient with non-small cell lung cancer. The patient underwent self expanding metallic esophageal ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 10 publications
0
14
0
1
Order By: Relevance
“…Four reports described perforation or erosion of the proximal end of the stent into the aorta at autopsy or emergent thoracotomy. [1][2][3][4][5] To the best of our knowledge, this is the first report of successful NBCA embolization and subsequent endovascular stent graft placement for treatment of an AEF secondary to placement of an esophageal stent.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Four reports described perforation or erosion of the proximal end of the stent into the aorta at autopsy or emergent thoracotomy. [1][2][3][4][5] To the best of our knowledge, this is the first report of successful NBCA embolization and subsequent endovascular stent graft placement for treatment of an AEF secondary to placement of an esophageal stent.…”
Section: Discussionmentioning
confidence: 91%
“…AEF caused by an esophageal stent is extremely rare; only a few cases have been reported. [1][2][3][4][5] To the best of our knowledge, this is the first report of the successful treatment of AEF secondary to esophageal stent placement with N-butyl 2-cyanoacrylate (NBCA) embolization and subsequent endovascular stent graft placement.…”
mentioning
confidence: 95%
“…The majority of patients present with a herald bleed, with catastrophic exsanguination delayed by hours to even months. 6,11 Other accompanying signs and symptoms include chest pain (75%), sepsis (53%), and back pain (18%). 4,17,18 Dysphagia and syncope occur less frequently.…”
Section: Discussionmentioning
confidence: 99%
“…Most involve treatment for esophageal malignancy, with reports of lung cancer being rare. 10,11 Radiation can cause damage to the aorta and other great vessels. [12][13][14][15] Poon et al demonstrated the radiation induced histological changes in a ruptured aorta in 1968, noting endothelial proliferation, intimal thickening, and vasa vasorum thrombosis leading to hyaline necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…[2] Aortoesophageal fistula has been previously described as a cause of mortality in irradiated subjects. [3] However, to the best of our knowledge, arteriovenous fistulae don′t represent a frequent vascular-related cause of mortality among patients who had received thoracic radiation therapy. Modern postmastectomy radiotherapy protocols are associated with a lower rate of thoracic complications without an increased locoregional recurrence risk.…”
Section: Discussionmentioning
confidence: 99%